Yield and physiological quality of common bean seeds as affected by manganese foliar application - Fernandes, Danilo Silveira; Soratto, Rogério Peres; Kulczynski, Stela Maris; Biscaro, Guilherme Augusto; Reis, Cleodir Jorge dos (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the effect of doses and time of manganese leaf application on yield and physiological quality of seeds on irrigated common bean, cultivar Pérola, grown in Typic Quartzipsamment. A randomized block design was used, in a factorial array 4x3 with four replications. The treatments were constituted by four doses of Mn (0, 150, 300, and 600 g ha-1) and three application times: R5 (pre-flowering), R6 (full flowering), and splitted half in R5 and half in R6. Even in Mn high content soil, the Mn leaf application increased the number of pods per plant, mass of 100 seeds and the seed yield of common bean. There was not difference among Mn leaf application in the pre-flowering and in the flowering stages. Common bean seeds germination was not affected by the time and doses of Mn leaf application. The emergency speed index decreased with Mn application.